(untitled) (The International Journal for Scientific Research, 2026)
Peer-assisted learning, a structured instructional approach in which learners work collaboratively in dyads or small groups to support each other’s academic development, has accumulated considerable empirical support as a means of enhancing reading achievement across diverse educational contexts. However, its application within Iraqi English as a Foreign Language (EFL) university classroom —and its effects on both reading comprehension and reading self-efficacy simultaneously—have not been systematically investigated. This study examines the effect of a structured Peer-Assisted Reading Activities (PARA) programme on the reading comprehension performance and reading self-efficacy beliefs of Iraqi EFL university learners. Employing a quasi-experimental pre- test/post-test non-equivalent control group design, the study involved 74 second-year undergraduate students at the University of Basrah, divided into an experimental group (n = 37) receiving a ten-week PARA intervention and a control group (n = 37) receiving conventional whole-class reading instruction. Reading comprehension was measured using a purpose-built instrument validated for the Iraqi EFL context; reading self-efficacy was assessed using an adapted version of the Reading Self-Efficacy Scale (RSES). Post-intervention analyses revealed statistically significant improvements in the experimental group on both dependent variables, with large effect sizes for reading comprehension (d = 1.74) and moderate-to-large effect sizes for reading self-efficacy (d = 1.12). Qualitative interview data further illuminate the mechanisms through which peer interaction facilitated comprehension development and self-efficacy enhancement, identifying collaborative sense-making, peer modelling, and reduced affective filter as central processes. The findings are interpreted through the lens of Vygotsky’s sociocultural theory, Bandura’s self-efficacy theory, and Peer-Assisted Learning Strategies (PALS) research, and carry significant implications for the redesign of EFL reading pedagogy in Iraqi higher education.